EFFECT OF IGNITION SYSTEM IN MOTORCYCLE TO PERFORMANCE AND EXHAUST GAS EMISSIONS WITH FUEL RON 88, RON 90, AND RON 92 - Julianto, Eko; Stiawan, Dony; Fuazen, Fuazen; Sarwono, Eko (Universitas Muhammadiyah Jakarta, 2020)
In the automotive field, the development of motorcycle ignition systems has been able to improve engine performance more fuel efficient. TCI has the advantage of transferring high voltage to the spark plug, the results issued from TCI are greater than the CDI system. To find out the results of motorcycle performance, namely the TCI ignition system and spark plugs on performance and exhaust emissions from motorcycles that use fuels such as Premium Ron 80, Pertalite Ron 90, and Pertamax Ron 92. Fuels that have octane that matches the bicycle motorcycles, in addition to the better performance of motorcycle engines, the fuel consumption is also more economical. In this study there are three variables, namely variations in rpm, performance and exhaust emissions. The results of the study of motorcycles that use the Ron 92 Pertamax fuel have far more torque and power than those that use the Ron 80 premium fuel and the pertalite Ron 90, while the HC levels produced by Ron 80 and 90 fuels tend to increase more than Ron fuel 92 which is between 65 - 228 ppm. CO2 levels were 12.53% while Pertamax was 10.74%, and pertalite was 11.17%, while the CO content produced was small at 3750 rpm resulting CO levels of 0.08 ppm. It can be concluded that the ignition produced is more stable which uses Pertamax fuel compared to using premium and pertalite fuel.